PERAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA STAFF TATA USAHA DI SEKOLAH DASAR - Sahputra, Hendra; Fitria, happy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— School administration is the spearhead of an institution's educational services, administration as a school administrative body that directly handles services inside and outside the school that has the task and function of carrying out operative work to achieve the goals of an organization, providing information for top leadership of the organization to make decisions or take appropriate action, and help smooth the development of the organization as a whole. Because of the importance of the performance of administrative staff for educational services in schools, it is therefore demanded by school principals who are able to maximize their role in efforts to improve the performance of administrative staff. This research was conducted at SD Negeri 29 Banyuasin III. Data collection tool in this study using interviews, observation, documentation and literary studies. The analysis technique uses descriptive quantitative analysis techniques. The results of the study stated that 1) the school principal had carried out his role through continuous training and gave full confidence to the administrative staff in managing school administration both administrative and information; 2) the performance of the administrative staff at SD Negeri 29 Banyuasin III has run effectively and has been carried out in accordance with the SOP standards of school administration; 3) the performance of administrative staff gives a positive impact on the smooth running of the school's core activities, namely teaching and learning activities. Keywords— Principal, Performance, Administration Abstrak— Tata usaha sekolah merupakan ujung tombak pelayanan pendidikan suatu lembaga, tata usaha sebagai badan administrasi sekolah yang secara langsung menangani pelayanan didalam internal maupun eksternal sekolah yang mempunyai tugas dan fungsi melayani pelaksanaan pekerjaan-pekerjaan operatif untuk mencapai tujuan dari suatu organisasi, menyediakan keterangan-keterangan bagi pucuk pimpinan organisasi untuk membuat keputusan atau melakukan tindakan yang tepat, dan membantu kelancaran perkembangan organisasi sebagai suatu keseluruhan. Karena pentingnya kinerja staff tata usaha bagi pelayanan pendidikan di sekolah, oleh karenanya dituntut kepala sekolah yang mampu memaksimalkan perannya dalam upaya meningkatkan kinerja staff tata usaha. Penelitian ini dilaksanakan di SD Negeri 29 Banyuasin III. Alat penumpul data dalam penelitian ini menggunakan wawancara, observasi, dokumentasi serta kajian literartur. Teknik analisis menggunakan teknik analisis kuantitatif deskriptif. Hasil penelitian menyatakan bahwa 1) kepala sekolah telah menjalankan perannya melalui pelatihan secara kontinu dan memberikan kepercayaan penuh kepada staff tata usaha dalam mengelola ketatausahaan sekolah baik yang bersifat administrasi maupun informasi; 2) kinerja staff tata usaha di SD Negeri 29 Banyuasin III sudah berjalan dengan efektif dan telah dilaksanakan sesuai dengan standar SOP ketatausahaan sekolah; 3) kinerja staff tata usaha memberikan dampak positif bagi kelancaran kegiatan inti sekolah yaitu kegiatan belajar mengajar Kata Kunci— Kepala Sekolah, Kinerja, Tata Usaha